2019
DOI: 10.7202/1056285ar
|View full text |Cite
|
Sign up to set email alerts
|

Behaving Badly: Critiquing the Discourses of “Children” and Their (Mis)Behaviours

Abstract: Discourses of children as deficient and deviant are common within the education system and shape the ways in which educators interact with and respond to children. To illustrate this, we conducted a critical discourse analysis of a provincial policy document that directs schools in the development of Codes of Conduct. Drawing on poststructural theory, we demonstrate the ways in which the discourses within policy construct and reify particular identities of the child and of misbehaviour and how these discourse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, this research has found that the policy documents analyzed often construct children in terms of deficiencies, with the schools' responses scripted accordingly in the language of disciplinary action or interventionist approaches. Janzen and Schwartz (2018) argue that "regulating, rejecting, or attempting to 'remedy' some children's identities, (mis)behaviours, and ways of being in the world, makes attending to power within schools an ethical issue" (p. 120). This requires that educators and policymakers consider the school system's potential complicity in a child's (mis)behaviour, including non-responsive curriculum, poor pedagogy, and rules that require conformity rather than supporting difference.…”
Section: Resultsmentioning
confidence: 99%
“…However, this research has found that the policy documents analyzed often construct children in terms of deficiencies, with the schools' responses scripted accordingly in the language of disciplinary action or interventionist approaches. Janzen and Schwartz (2018) argue that "regulating, rejecting, or attempting to 'remedy' some children's identities, (mis)behaviours, and ways of being in the world, makes attending to power within schools an ethical issue" (p. 120). This requires that educators and policymakers consider the school system's potential complicity in a child's (mis)behaviour, including non-responsive curriculum, poor pedagogy, and rules that require conformity rather than supporting difference.…”
Section: Resultsmentioning
confidence: 99%
“…It is also noted in the section requiring the Authority Board to develop a "respect for human diversity" policy, which is a requirement of the Manitoba Human Rights code (Legislative Assembly of Manitoba, 2021, p. 120). However, the diversity policy to be developed is required to include only two things: first, that teachers and staff receive training about bullying, subsequently constructing diversity as a problem that results in bullying-which is a grossly narrow assumption that considers student misbehaviour as bullying in the first place (Janzen & Schwartz, 2018). The second requirement is that schools are to "accommodate the establishment of student groups" (p. 121) that promote equity, such as gay-straight alliances.…”
Section: The Student In Relation To Othersmentioning
confidence: 99%
“…Moreover, the stigma of being in care is magnified by and intertwined with other identity markers such as race and poverty, or by a child's "mis"behaviours (Janzen and Schwartz, 2018), reverberating through additional layers and lenses further delimiting recognizability. This is particularly salient in Manitoba and in Canada where the numbers of children in care are disproportionately Indigenous (First Nations, Métis, or Inuit), and who are often disproportionately affected by poverty.…”
Section: What Does Stigma Do?mentioning
confidence: 99%